2020
DOI: 10.1111/1750-3841.15503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different drying methods on the structures and functional properties of phosphorylated Antarctic krill protein

Abstract: Antarctic krill protein (AKP) was extracted from Antarctic krill by an alkali dissolution‐isoelectric precipitation method and then it was phosphorylated with sodium tripolyphosphate. The phosphorylated Antarctic krill protein (P‐AKP) powder was obtained by spray‐drying (SD), freeze‐drying (FD), and hot‐air drying (AD), and the effects of these drying methods on the structures and functional properties of proteins were investigated. The P‐AKP powder dried by SD had the best sensory performance, and its particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Sulfhydryl content is an essential conformational aspect in many proteins, which affects the functional changes of proteins. Some processing methods, such as heating and high pressure, might cause changes and destruction of sulfhydryl content, which can significantly affect the functional properties of proteins ( Lin et al, 2020 ). The total sulfhydryl, free sulfhydryl, and disulfide bond content of samples are shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sulfhydryl content is an essential conformational aspect in many proteins, which affects the functional changes of proteins. Some processing methods, such as heating and high pressure, might cause changes and destruction of sulfhydryl content, which can significantly affect the functional properties of proteins ( Lin et al, 2020 ). The total sulfhydryl, free sulfhydryl, and disulfide bond content of samples are shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was mainly attributed to a higher temperature of the MD process during drying treatment, which significantly promoted the formation of disulfide bonds. Lin et al (2020) indicated that the higher drying temperature could enhance the extent of protein denaturation, which subsequently resulted in increased disulfide bond contents. Moreover, the low temperature or freezing stresses could also promote the occurrence of protein denaturation to different extents, which led to obviously higher disulfide bond contents of the FD group than ND group ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations